The Effect of Tiktok Social Media on Student Learning Achievement in Class VIII Informatics Subjects at SMP Negeri 22 Samarinda - Febby Mahita Putri P. C.; Dewi Rosita; I Wayan Sugianta N (TEPIAN, 2024)
The study aims to determine the effect of TikTok social media on student learning achievement in informatics subjects using correlational quantitative methods. Total of 82 respondents were used as the research sample who were seventh grade students of SMP Negeri 22 Samarinda with the top ten rankings. Data collection techniques using questionnaires, documentation and observation. The questionnaire instrument used a Likert scale. The analysis used normality test, linearity test, simple linear regression test and t test. The results of the partial regression significance test (t test) sig. variable X (TikTok Social Media) is 0.000 <0.05 and the t value is 8,188> t table 1. 99006, there is a significant influence of the independent variable TikTok social media (X) on the dependent variable learning achievement (Y), it can be concluded that Ha is accepted while Ho is rejected, there is a significant relationship between TikTok social media and learning achievement, it can be concluded that there is a significant influence between TikTok social media on student learning achievement in Class VIII Informatics subjects at SMP Negeri 22.